Social Choice (Routledge Revivals). - Liebermann, Bernhardt (Routledge revivals., 2012)
First published in 1971, Social Choice is both a text and reference containing the proceedings of a conference dealing with contemporary work on the normative and descriptive aspects of the social choice problem. This reissue will be of interest to advanced undergraduate and graduate courses on group decision making and social choice. Economists, social psychologists, political scientists and sociologists will welcome this valuable work.